Association between physical frailty and cortical structure in middle-aged and elderly people: a Mendelian randomization study - Zhang, Xin; Wang, Zhen; Zou, Jing; Zhang, Le; Ning, Jing-Hua; Jiang, Bei; Liang, Yi; Zhang, Yu-Zhe (Frontiers in Aging Neuroscience, 2024)
An association between physical weakness due to aging and cortical structure has been reported in middle-aged and older adults. However, the exact cause of this effect remains to be investigated. In this study, we utilized Mendelian randomization (MR) analysis to examine the impacts of frailty exposure factors on various regions of the cerebral cortex. We utilized GWAS data on frailty from the UK Biobank and obtained GWAS data for various brain regions from the ENIGMA consortium. Most of the study's results focused on the effects on cortical surface area, and these effects were found to be facilitative. However, the effects on cortical thickness were not significant. Although our study reveals factors that may affect cortical structure, further investigation is needed to determine whether these alterations in brain structure are related to brain diseases in middle-aged and older adults. What is certain is that the physical frailty that accompanies aging in humans poses a significant threat to the quality of life and life expectancy of middle-aged and older adults.